2010
DOI: 10.1061/(asce)gt.1943-5606.0000324
|View full text |Cite
|
Sign up to set email alerts
|

Compaction Characteristics of Municipal Solid Waste

Abstract: Compaction characteristics of municipal solid waste �MSW� were determined in the laboratory and in the field as a function of moisture content, compactive effort, and seasonal effects. Laboratory tests were conducted on manufactured wastes using modified and 4X modified efforts. Field tests were conducted at a MSW landfill in Michigan on incoming wastes without modifications to size, shape, or composition, using typical operational compaction equipment and procedures. Field tests generally included higher effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 6 publications
(1 reference statement)
4
48
0
2
Order By: Relevance
“…Mat. & Env., DOI: https://doi.org/10.21660/2018.44.7108 ISSN: 2186-2982 (Print), 2186-2990 (Online), Japan while compressibility increases when water was added [5]. Clay mineralogy affects the coefficient of consolidation (Cv).…”
Section: Introductionmentioning
confidence: 99%
“…Mat. & Env., DOI: https://doi.org/10.21660/2018.44.7108 ISSN: 2186-2982 (Print), 2186-2990 (Online), Japan while compressibility increases when water was added [5]. Clay mineralogy affects the coefficient of consolidation (Cv).…”
Section: Introductionmentioning
confidence: 99%
“…Both Powrie and Beaven (1999) and Beaven (2000) observed an increase in average particle density with increasing average stress and concluded that such a relationship was not surprising Beaven (2000) for pulverized waste, where the particle density increased from 0.59 to 0.93 Mg/m 3 with an increase in average stress from 35 to 486 kPa. Hanson et al (2010a) suggested that specific gravity and unit weight increased with increasing compactive effort. Hanson et al (2010a) determined the specific gravity of MSW through back calculation methods.…”
Section: Specific Gravity Of Mswmentioning
confidence: 99%
“…Hanson et al (2010a) suggested that specific gravity and unit weight increased with increasing compactive effort. Hanson et al (2010a) determined the specific gravity of MSW through back calculation methods. A G s value of 1.6 was back calculated using laboratory compaction curves generated using 4X modified effort.…”
Section: Specific Gravity Of Mswmentioning
confidence: 99%
See 2 more Smart Citations